African economic development: what role can the G20 Compact play? - Rainer Thiele; Maximilian Köster; Ikechukwu Okoli; Friederike Rühmann (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Under the German Presidency of the G20 in 2017, the Compact with Africa (CWA) was launched with the goal of mobilising private capital and promoting the efficient use of public resources so as to increase private and infrastructure investment in Africa. In this discussion paper, we provide a critical assessment of the role that the CWA could play for African development. We argue that, despite some positive developments since the early 2000s, Africa's future prospects for sustained and inclusive economic growth remain highly uncertain, and that the CWA has the potential to help address key remaining bottlenecks. Yet, it is far from clear whether the CWA will live up to expectations. We find that, despite its potential to bring important structural benefits and financial flows to Africa, the overall scope of the CWA investment concept is rather limited. Most notably, investments in education and, in particular, vocational training might limit the CWA's success when it comes, for example, to tackling youth unemployment. Furthermore, judged against its recognition of the goals of the 2030 Agenda for Sustainable Development, the CWA too narrowly focusses on achieving economic growth in Africa. To bring the CWA more closely in line with the 2030 Agenda, it should at least be ensured that the likely poverty impacts of the investment programmes are systematically assessed so as to render them as pro-poor as possible. Since African livelihoods critically depend on environmental conditions such as clean water and a stable climate, the possible negative externalities of investments should also explicitly be taken into account when implementing the CWA. Another problem relates to the criteria that countries have to meet in order to qualify for participation in the CWA. As shown for the example of Nigeria, it is hard to assess what it takes to enter an agreement. Finally, the CWA can only be successful if both the G20 members and the African partners take responsibility for it. It is reasonable to be sceptical of whether the commitment to support the CWA goes beyond the German G20 Presidency. While being interested in fostering private investments and infrastructure in Africa, major players within the G20 appear to have their own interests and approaches that might compete with the CWA. It should be acknowledged that the G20 countries emphasise African ownership. Yet, a thorough approach to strengthen African ownership would have built more widely on local initiatives such as the Agenda 2063, rather than setting up a new scheme exogenously. However, as the CWA will not be reversed, it is crucial to ensure that it goes together with local interests and priorities.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung; Entwicklungsfinanzierung und öffentliche Finanzen